Forecasting the central bank's inflation objective is a good rule of thumb - Marie Diron; Benoît Mojon (European Central Bank (ECB), 2005)
This paper first shows that the forecast error incurred when assuming that future inflation will be equal to the inflation target announced by the central bank is typically at least as small and often smaller than forecast errors of model-based and published inflation forecasts. It then shows that there are substantial benefits in having rule-of-thumb agents who simply trust that the central bank will deliver its pre-announced inflation objective.
Keywords: E5; 330; credibility; inflation forecast; inflation targeting; monetary policy; Geldpolitik; Glaubwürdigkeit; Zentralbank; Inflationssteuerung; Inflationserwartung; EU-Staaten; OECD-Staaten